COASTAL VULNERABILITY STUDY IN CENTRAL JAVA PROVINCE AND YOGYAKARTA SPECIAL REGION AND COASTAL INUNDATION RISK IN PATI REGENCY - Fernando Setyono, Jovan
The coastal hazards that are threatening the coasts of Central Java and Yogyakarta Special Region have long posed a threat to coastal sustainability, including erosion, sea level rise, and other detrimental physical parameters. The quantification of coastal vulnerability levels was conducted using the Coastal Vulnerability Index (CVI) method, approximating real conditions with seven physical parameters to differentiate vulnerability between the northern and southern coasts. The distribution of coastal vulnerability index, approximated by CVI, indicates that vulnerability in the southern coast tends to be more vulnerable compared to the northern coast due to the primary factors, coastal protection and erosion rates. The highest vulnerability values (level 5) are 44,82% for the southern coast and 30,77% for the northern coast. Although the cities/districts that are vulnerable to coastal hazards are Purworejo, Kebumen, Kulonprogo, and Bantul on the southern coast, and Brebes, Demak, Jepara, and Kendal on the northern coast, a case study of Pati Regency was chosen due to the lack of information and studies on coastal flooding, enabling the determination of risk levels by approximating inundation under various scenarios (using a bathtub model) induced by population vulnerability (land vulnerability index/LVI). The area of inundation in Pati Regency under each scenario is 10,600 ha (scenario 1), 12,481 ha (scenario 2), 14,593 ha (scenario 3), and 18,679 ha (scenario 4), with the most vulnerable subdistrict is Juwana, which would be submerged by 75% of its total area in scenario 4. Land vulnerability in Pati Regency is very low in upstream areas and high in downstream areas, resulting in high maximum risk levels due to inundation hazards induced by inland flooding in scenarios 3 and 4, with the highest risk area covering 1,300 ha for scenario 3 and 1,736 ha for scenario 4.